1998
DOI: 10.1093/hmg/7.11.1725
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genes Encoding Translation Initiation Factor eIF-2  in Mouse and Human: Sex Chromosome Localization, Escape from X-Inactivation and Evolution

Abstract: The Delta Sxrb interval of the mouse Y chromosome is critical for spermatogenesis and expression of the male-specific minor transplantation antigen H-Y. Several genes have been mapped to this interval and each has a homologue on the X chromosome. Four, Zfy1 , Zfy2 , Ube1y and Dffry , are expressed specifically in the testis and their X homologues are not transcribed from the inactive X chromosome. A further two, Smcy and Uty , are ubiquitously expressed and their X homologues escape X-inactivation. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 48 publications
5
57
0
Order By: Relevance
“…DOI: 10.1371/journal.pgen.0020043.g006 many orders but absent in mouse and pig [2]. Conversely, Eif2s3y and Ube1y are Y-borne in mouse, cat, pig, and other eutherians but absent in human and some related primate lineages [2,6,12]. Our analysis of the feline Y chromosome revealed novel X-degenerate genes, including CUL4BY, whose counterpart, CUL4BX, is positioned in X chromosome Stratum 1 [26,27], and likely originated early in mammalian evolution and subsequently was lost in the human and probably rodent lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOI: 10.1371/journal.pgen.0020043.g006 many orders but absent in mouse and pig [2]. Conversely, Eif2s3y and Ube1y are Y-borne in mouse, cat, pig, and other eutherians but absent in human and some related primate lineages [2,6,12]. Our analysis of the feline Y chromosome revealed novel X-degenerate genes, including CUL4BY, whose counterpart, CUL4BX, is positioned in X chromosome Stratum 1 [26,27], and likely originated early in mammalian evolution and subsequently was lost in the human and probably rodent lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative mapping studies have shown that most eutherian orders share a core set of conserved, X-degenerate, Y-borne genes [6,7,[10][11][12][13][14][15][16]. Previous studies mapped eight of these to the feline Y chromosome [13], but efforts to isolate additional feline Y-borne loci were largely unsuccessful, primarily due to mammalian conserved X-Y primers preferentially amplifying only X-specific homologs in male cat DNA.…”
Section: Isolation and Mapping Of New Feline X-degenerate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mouse Smcy and Uty and mouse and human Eif2s3x are known to escape X-inactivation. 23,24 However, previous data indicate that Mecp2 does not escape X-inactivation in both humans 25 and mice. 26 Therefore, escape from X-inactivation is not likely responsible for sex differences in rat Mecp2 expression.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 92%
“…Eif2s2 is a TGCT modifier in mice (Heaney et al, 2009), but remains to be confirmed in humans. Eif2s3 is located on both Y (Eif2s3y) and X (Eif2s3x) chromosomes in mice (in humans, no Y homologues have been found) (Ehrmann et al, 1998). Given the role of sex chromosomes discussed above, Eif2s3 should be considered as a candidate for TGCT susceptibility.…”
Section: Rna Biology Epigenetic Regulation and Tgctsmentioning
confidence: 99%